PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK PADA MATERI MENYIMAK TEKS CERITA RAKYAT PADA SISWA KELAS IV SEKOLAH DASAR - Suci Erhami; Hetilaniar; Aldora Pratama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to produce a flipbook learning media product on listening to folklore texts in grade IV elementary school students that is valid and practical. This research uses research and development methods (Research and Development) using the ADDIE development model which consists of 5 (five) stages, namely the analysis stage, planning stage, development stage, implementation stage and evaluation stage. The subjects in this study were grade IV students of SD Negeri 3 Semende Darat Laut. The results of data analysis based on the validation of flipbook learning media conducted by expert experts consisting of media experts, linguists and material experts obtained an average validation score with a percentage of 86.7% showing that flipbook learning media in the material listening to folklore texts developed was included in the "very valid" category. Based on the results of the questionnaire, student responses that have been tested obtained an average value of practicality with a percentage of 85.7%, indicating that the flipbook learning media developed is included in the category of "very practical". The results of students' scores on the postest obtained an average score of 96% with the category "very decent". Based on the results of validation by expert experts, the results of practicality trials by students and posttest results, it can be concluded that the flipbook learning media on the material for listening to folk terita texts in grade IV elementary school students is suitable for use in learning on theme 8 of the area where I live subtheme 1 the environment where I live learning 1.